The Importance of the Spiritual Potential In the Development of Education and Society in the New Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
in the article, the author describes the role of reforms carried out in the educational system in New Uzbekistan in social development, the idea of turning the country into a prosperous and prosperous state with strong potential, a decent reputation in the world arena, and also explains that it is a holistic spiritual foundation that unites our people in the direction of common goals.